REACHING YOUTH WITH RELIABLE INFORMATION DURING THE COVID-19 PANDEMIC: “SOCIAL MEDIA FOR SURE” - Hawke, Lisa D.; Daley, Mardi; Relihan, Jacqueline; Semansky, Paris; Sheth, Maya S.; Henderson, Joanna (International Journal of Child, Youth and Family Studies, 2023)
As the COVID-19 pandemic evolves, it is important to continue providing accurate updates and public health information to various target audiences. In support of such efforts, this study aims to understand how youth have accessed information about COVID-19 and to record their perspectives on how such information is best communicated. As part of a larger longitudinal study, 463 youth (M = 21.2 years, SD = 2.2) were surveyed about their sources of information on COVID-19, with qualitative questions regarding their perspectives on optimal public health communication strategies. A majority of youth reported using online sources to access information about COVID-19, including online news sources and social media. They used a diversity of such sources, with a preference those they regarded as reliable. Participants recommended that public health information campaigns be conducted on a variety of social media channels. Other digital campaigns were also recommended, while some suggested providing information through schools. Information should be brief, engaging, accessible, and frequently updated, using verified sources to ensure accuracy. We conclude that, to reach youth effectively, it is essential that accurate COVID-19 information and public health guidelines be disseminated in an engaging manner using digital means, particularly social media. Communication campaigns should be developed in partnership with youth in order to best reach this audience with the information they need.